Creative Tourism Delivery in Action: A Comparative Study of Phuket and Bandung - Naomi Nethania; Rini Andari; Gita Siswhara (Universitas Pendidikan Indonesia, 2024)
The aim of this study is to provide a comprehensive explanation of how creative tourism has been implemented in Braga Street, Bandung, Indonesia, and Phuket Old Town, Phuket, Thailand. The study used a descriptive qualitative method, which included in-depth observations of the destinations, an analysis of literature, and online articles about the development of creative tourism in these cities.The study included three months of direct observations at each destination, as well as a literature review of more than 50 articles on creative tourism. The results highlight the diverse forms of creative tourism delivery in both locations, emphasizing events, networks, partnerships, and creative entrepreneurs as key elements. The findings indicate that Braga Street effectively integrates art, culinary, and shopping tourism, whereas Phuket Old Town emphasizes gastronomic tourism through various annual events and markets. This suggests that by capitalizing on their unique cultural elements and fostering collaborative networks, both destinations can significantly enhance their attractiveness and contribute to the development of sustainable tourism.